Unrelenting innovation : how to build a culture for market dominance - Tellis, Gerard J., 1950- (Warren Bennis signature series., 2013)
The hands-on guide for fostering relentless innovation within your company Gerard Tellis, a noted expert on innovation, advertising, and global markets, makes the compelling case that the culture of a firm is the crucial driver of an organization's innovativeness. In this groundbreaking book he describes the three traits and three practices necessary to create a culture of relentless innovation. Organizations must be willing to cannibalize successful products, embrace risk, and focus on the future. Organizations build these traits by providing incentives for enterprise, empowering product champions, and encouraging internal markets. Spelling out the critical role of culture, the author provides illustrative examples of organizations with winning cultures and explores the theory and evidence for each of the six components of culture. The book concludes with a discussion of why culture is superior to alternate theories for fostering innovation. Offers a groundbreaking take on innovation that is driven by a company's culture Shows what it takes to create a culture of innovation within any organization Based on a study of 770 companies across 15 countries, the origin of 90 radical innovations spanning over 100 years, and the evolution of 66 markets spanning over a 100 years Provides numerous mini cases to illustrate the workings of culture Written by Gerard Tellis director of the Center for Global Innovation This must-have resource clearly shows the role of culture in driving relentless innovation and how to foster it within any organization.